Erster Beitrag zur Kenntnis der Verbreitung der mitteleuropäischen Proctotrupoidea (mit besonderer Berücksichtigung von Südbaden) 1. Diapriidae: Belytinae. - Wall, Ingmar (Contributions to Entomology = Beiträge zur Entomologie, 1963)
There are summarized species of the subfamily Belytinae (Fam. Diapriidae) collected at five Central-European localities (especially around St. Blasien, Black Forest, W-Germany). Comparing the different biotops and the Belytinae found there (with regard to the other Proctotrupoidea) the author could state that these insects are generally frequent at localities which are characterized by low illumination, a closed low vegetation, and a moderately high degree of moisture.